2005
DOI: 10.1007/s00213-005-0005-8
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin synthesis inhibition reveals distinct mechanisms of action for MDMA and its enantiomers in the mouse

Abstract: The effects of S(+)-MDMA on core temperature and head twitch behavior are consistent with a mechanism involving 5-HT release, whereas the effects of R(-)-MDMA on head twitch behavior are consistent with a direct agonist mechanism of action. The actions of the racemate on core temperature and locomotor activity likely involve a combination of 5-HT release and direct agonism at 5-HT receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 23 publications
4
25
0
1
Order By: Relevance
“…However, it remains difficult to explain the capacity of each MDMA enantiomer to substitute for one another in mice, using procedures identical to those herein described previously . Nevertheless, these present findings suggesting qualitatively distinct discriminative stimulus effects in the mouse are supported not only by earlier drug discrimination experiments in the rat, but also by previous studies where S(ϩ)-MDMA elicited stimulant-like effects, while R(Ϫ)-MDMA induced hallucinogen-like effects, on multiple behavioral and physiological endpoints in mice (Fantegrossi et al, 2003(Fantegrossi et al, , 2005a.…”
Section: Discriminative Stimulus Effects Of Mdma Isomers In Mice 721supporting
confidence: 88%
See 1 more Smart Citation
“…However, it remains difficult to explain the capacity of each MDMA enantiomer to substitute for one another in mice, using procedures identical to those herein described previously . Nevertheless, these present findings suggesting qualitatively distinct discriminative stimulus effects in the mouse are supported not only by earlier drug discrimination experiments in the rat, but also by previous studies where S(ϩ)-MDMA elicited stimulant-like effects, while R(Ϫ)-MDMA induced hallucinogen-like effects, on multiple behavioral and physiological endpoints in mice (Fantegrossi et al, 2003(Fantegrossi et al, , 2005a.…”
Section: Discriminative Stimulus Effects Of Mdma Isomers In Mice 721supporting
confidence: 88%
“…On a behavioral level, S(ϩ)-MDMA, but not R(Ϫ)-MDMA, elicits hyperthermia and locomotor activity in mice (Fantegrossi et al, 2003). Furthermore, only R(Ϫ)-MDMA induces head-twitch behavior in mice through direct agonism of the 5-HT 2A receptor (Fantegrossi et al, 2005a). This work is buttressed by studies using drug discrimination-the preclinical analog of subjective effects (Schuster and Johanson 1988;Brauer et al, 1997)-in rats.…”
mentioning
confidence: 99%
“…Likewise, the lethal effects of R(Ϫ)-MDMA are less potent than those of S(ϩ)-and racemic MDMA in mice (Fantegrossi et al, 2003), and R(Ϫ)-MDMA is 4-fold less potent than S(ϩ)-and racemic MDMA in suppressing operant responding in the mouse (Glennon et al, 1987). Such potency differences are not universally reported, however, because head twitch behavior elicited by S(ϩ)-and R(Ϫ)-MDMA occurs over a comparable dose range (Fantegrossi et al, 2005).…”
Section: Discussionmentioning
confidence: 98%
“…Thus, the reciprocal generalization here reported between S(ϩ)-and racemic MDMA is consistent with these and other in vivo comparisons of these drugs. Likewise, both enantiomers of MDMA elicit head twitch behavior in the mouse, albeit via different mechanisms (Fantegrossi et al, 2005), so it was not entirely unexpected that both S(ϩ)-and R(Ϫ)-MDMA would substitute for each other. …”
Section: Discussionmentioning
confidence: 99%
“…We also found that MDMA induces smoother movement patterns with fewer directional changes (Paulus and Geyer, 1992;Powell et al, 2004) and that these effects are mimicked by other 5-HT releasers such as MBDB and a-ethyltryptamine (Callaway et al, 1991(Callaway et al, , 1992Krebs and Geyer, 1993). In mice, 5-HT depletion by parachlorophenylalanine treatment or 5-HT 1B gene deletion does not block locomotor activity increases induced by high doses of MDMA, indicating that some of the effects on locomotor activity are via direct agonism at 5-HT receptors or via other neurotransmitter systems (Fantegrossi et al, 2005;Scearce-Levie et al, 1999).…”
Section: Introductionmentioning
confidence: 99%